Dr. Miguel Ángel Moreno Rodríguez. Clinical model for Internal Medicine - Osmín Hernández Azcuy; Miguel Ángel Blanco Aspiazu; Celia Viera Machado (Universidad de Ciencias Médicas de La Habana, 2019)
Professor Miguel Ángel Moreno Rodríguez was a model of clinician, devoted to medical care and teaching in the Internal Medicine specialty. His Curriculum Vitae shows his outstanding work as a professional, internist and revolutionary. He was a paradigm for the new generations of doctors who love the Medical Clinics. Keywords: Internal Medicine, clinics, moral values, military medicine, history.